Effects of Gibberellin on Physical and Chemical Quality of Oil Palm (Elaeis guineensis Jacq.) Fresh Fruit Bunches - Ramanis, Imelya; Sudradjat, Sudradjat; Saprudin, Deden (Journal of Tropical Crop Science, 2023)
The quality of crude palm oil (CPO) is influenced by the quality of fresh fruit bunches, crop culture, and postharvest handling. A delay in fruit processing can cause physical damages to the fresh fruit bunches. Gibberellic acid (GA3) can potentially reduce the physical damage due to delayed processing of the fresh fruit bunches. Our study aims to determine how GA3 affects the physical and chemical quality of oil palm fresh fruit bunches. The fresh fruit bunch samples were collected from the IPB-Cargill Palm Oil Education and Research, Jonggol, Bogor, Indonesia. This study used a randomized complete block design that consisted of four concentrations of GA3: 0, 12.5, 25 and 37.5 ppm. GA3 application reduced fruit loss, respiration rate, and maintain fruit moisture and firmness, increased the oil content, and stabilize the free fatty acid content. GA3 concentration of 12.5 ppm is the optimal concentration. Based on the correlation analysis, fruit softness has a strong correlation with free fatty acids.